Journalistic discourse historical fiction by A. Alimzhanov (Eurasian Journal of Philology Science and Education, 2015)
In the article on the material of historical novels by A.Alimzhanov discusses the features of his journalistic discourse. Reveals two major trends: the trend highlight the authorial "I" as an extra-linguistic categories, characterized by extreme openness of citizenship by a full merger votes author and character. The second trend is associated with many historical reminiscences, creating storylines, claiming the complex dialectics of past and present, personal and social. The analysis allowed to identify theoretical and practical significance for the modern historical prose problem strengthen journalistic start. The article draws parallels between novels A.Alimzhanova different years, based on an analysis of their discourse about the importance of the conclusion of the works of historical figures purely journalistic means of representation. The novels of Alimzhanova, relying directly on the historical realities of the time Makhambet and al-Farabi, at the same time carry the characteristics of artistic vision writer living problems of his time.
Keywords: discourse; author; novel; story; journalistic; historical; aesthetic.